HMG-CoA Reductase Inhibitors from Monascus-Fermented Rice - Xuemei Li; Chunli Liu; Zhenwen Duan; Shuren Guo (Journal of Chemistry)
Seven compounds were isolated from Monascus-fermented rice by column chromatography with silica gel and semiprep HPLC. Their structures were elucidated by extensive spectroscopic methods. All compounds displayed HMG-CoA reductase inhibitory potential, among them compound 7 exhibited strong inhibition with IC50 value comparable with lovastatin. In this study, two compounds (1 and 2) were obtained from natural source for the first time.